Hierarchical pore ozone decomposition catalyst as well as preparation method and application thereof

By adopting a multi-stage pore structure of ozone decomposition catalyst and using the multi-stage pore structure of support and nanometal oxide, the problem of catalyst inactivation under an aqueous atmosphere is solved, and efficient ozone decomposition performance and stability are achieved.

CN119633804APending Publication Date: 2025-03-18DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411747813.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The existing ozone catalysts have problems of reversible inactivation and irreversible inactivation under an aqueous atmosphere, which affects their stability and ozone decomposition properties.

Method used

An ozone decomposition catalyst with a multi-stage pore structure is adopted. The catalyst consists of a support and nanometal oxide. The support has a large mesoporous structure and the nanometal oxide has a small mesoporous structure to form a multi-stage pore structure, which improves the stability of the catalyst and the ozone decomposition performance.

Benefits of technology

Under an aqueous atmosphere, the ozone decomposition performance of the multi-stage pore ozone decomposition catalyst remains excellent, avoiding the reversible and irreversible deactivation of the catalyst, and improving its stability and application range.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119633804A_ABST
    Figure CN119633804A_ABST
Patent Text Reader

Abstract

The invention discloses a hierarchical pore ozone decomposition catalyst as well as a preparation method and application thereof. The hierarchical pore ozone decomposition catalyst comprises a carrier and a nano metal oxide, the carrier contains primary mesopores, and the pore diameter of the primary mesopores is 10 nm to 50 nm; the nano metal oxide contains secondary mesopores, and the pore diameter of the secondary mesopores is 2 nm to 10 nm; the nano metal oxide is distributed on the surface of the carrier or in primary mesopores in the carrier; the nano metal oxide contains an oxide of metal manganese or a mixture of the oxide of metal manganese and an oxide of metal M; the metal M is selected from at least one of Cu, Co and Ni; the component of the carrier is selected from at least one of Al2O3 (aluminum oxide), SiO2-Al2O3 (silicon oxide) and TiO2-Al2O3 (titanium oxide). The catalyst has excellent ozone catalytic decomposition performance, and especially under a water-containing atmosphere, the ozone decomposition performance can still be maintained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a multi-stage porous ozone decomposition catalyst, a preparation method and application thereof, and belongs to the technical field of catalyst preparation. Background Art

[0002] Typical air pollutants NOx and VOCs undergo photochemical reactions to generate ozone. In recent years, ozone pollution has intensified and has become a major air pollution problem. Ozone has strong oxidizing properties, and prolonged exposure to high-concentration ozone can cause serious harm to the human body. The Ambient Air Quality Standard (GB 3905-2012) stipulates that the maximum 8-hour average concentration of ozone per day is limited to 100 μg / m 3 The secondary limit is 160 μg / m 3 Studies have shown that the maximum concentration of ozone that humans can accept within one hour is 260 μg / m 3 At 320μg / m 3 Being active in an ozone environment for 1 hour will cause coughing, breathing difficulties and decreased lung function. In addition, ozone is also widely used in sewage treatment and disinfection and inactivation processes. The release of residual ozone in these processes will also endanger human health. Near-ground ozone pollution can be eliminated by thermal decomposition, liquid absorption, solid adsorption, electromagnetic radiation decomposition, photocatalysis and catalytic decomposition. In comparison, the catalytic decomposition method has the advantages of high treatment efficiency and no secondary pollution. It is particularly suitable for catalytic removal of ozone in aircraft cabins with large air volume and low concentration. When the aircraft is at cruising altitude, the ozone concentration in the atmosphere outside the cabin is 1.72ppm. At this time, ozone will enter the cabin through the engine air intake system, and the ozone concentration in the aircraft cabin will reach 0.14ppm. In 1971, the US Environmental Protection Agency (EPA) established the primary and secondary standards for ozone concentration, with an upper limit of 80ppb. In 2015, EPA further lowered the 8-hour ozone concentration standard to 70ppb. The EU's "daily maximum 8-hour average" of ozone has been reduced to 60ppb in 2010; my country's newly revised "Ambient Air Quality Standards" in 2012 also added control standards for ozone: the daily maximum 8-hour average is 50ppb for level 1 and 80ppb for level 2. In order to meet the relevant standards, modern large passenger aircraft are equipped with ozone converters to solve the problem of ozone pollution and hazards.

[0003] Ozone decomposition catalysts can be transition metal oxide catalysts such as MnO2, NiO, Cu2O, CeO2, or precious metal catalysts such as Pd, Pt, Rh, Ag, Au, and Ru. Among them, Pd and Mn have higher catalytic ozone decomposition performance, and the carrier can be selected from SiO2, Al2O3, activated carbon, TiO2, molecular sieves, mordenite, etc. Related studies have found that ozone decomposition performance is related to the nature and number of oxygen defects on the catalyst surface. The formation energy of oxygen defects on the surface of MnOx with different valence states (β-MnO2, α-Mn2O3, Mn3O4) is different. The formation energy of oxygen defects on the surface of β-MnO2 is the lowest, and it has the highest ozone decomposition activity. The content of oxygen defects on the surface of MnO2 is also an important factor affecting the ozone decomposition performance. The oxygen defects on the surface of metal oxides can be effectively regulated by reduction treatment, transition metal or nitrogen doping. For example, doping MnOx with transition metal elements such as Co, Cu, Ce and nitrogen can significantly increase the oxygen defect content and activity on the surface of MnOx, improve the desorption ability of decomposed intermediate oxygen species, and improve the catalytic ozone decomposition performance and water resistance. Similarly, nitrogen doping improves the specific surface area, number of acidic sites and oxygen vacancy content of MnO2, while maintaining the crystal structure of α-MnO2 and improving the ozone decomposition performance of MnO2. The N distributed on the surface of nitrogen-doped MnO2 enhances its binding force with Pd, which helps to highly disperse the Pd in ​​its loaded Pd catalyst (Pd-NMnO2), and improves its ozone catalytic decomposition activity and stability. However, it was found in the above study that although the ozone catalytic decomposition performance of the catalyst under wet conditions was improved to a certain extent by doping modification, the competitive adsorption of water molecules and the dissociative adsorption of water molecules at defect sites to generate strongly adsorbed hydroxyl groups in a water-containing atmosphere will still lead to reversible and irreversible deactivation of the catalyst. Studies have also found that carboxyl groups have a preferential absorption effect on water vapor molecules, which will reduce the competitive adsorption effect of water. Therefore, some scholars introduced carboxyl groups through acrylic acid-modified non-woven fabrics, and then loaded MnOx to improve the catalytic decomposition performance of ozone under water-containing conditions (Environmental Science and Pollution, 2023, 30: 17994-18013.). In addition, carboxyl groups can also promote the oxidation and decomposition of ozone, but carboxyl groups are easily oxidized by ozone for a long time, and their promoting effect disappears. Therefore, in order to solve the stability of ozone catalysts in a water-containing atmosphere, it is also necessary to adjust its microstructure. Summary of the invention

[0004] According to one aspect of the present application, a multi-level porous ozone decomposition catalyst is provided. The carrier in the catalyst has a rich large mesoporous structure; in the large mesoporous channels, a metal oxide nanolayer with a small mesoporous structure is constructed to form a catalyst with a multi-level porous structure. The catalyst has excellent ozone catalytic decomposition performance, especially in a water-containing atmosphere, the ozone decomposition performance can still be maintained.

[0005] The multi-level porous ozone decomposition catalyst comprises a carrier and nano metal oxide;

[0006] The carrier contains primary mesopores, the pore size of which is 10nm to 50nm; the nano-metal oxide contains secondary mesopores, the pore size of which is 2nm to 10nm;

[0007] The nano-metal oxide is distributed on the surface of the carrier or in the primary mesopores of the carrier;

[0008] The nano metal oxide contains metal manganese oxide or a mixture of metal manganese oxide and metal M oxide; the metal M is selected from at least one of Cu, Co, and Ni;

[0009] The component of the carrier is selected from at least one of Al2O3, SiO2-Al2O3, and TiO2-Al2O3.

[0010] Preferably, the average pore size of the primary mesopores is 11 nm to 30 nm; the average pore size of the secondary mesopores is 4 nm.

[0011] That is, the nano metal oxide can be a single metal manganese oxide MnO x Or a mixture of metal manganese and metal M oxide Mn-MO x (M = one of Cu, Co, Ni or a combination of two of them.) The component of the carrier may be Al2O3 alone, or a mixed oxide consisting of SiO2 or TiO2 and Al2O3.

[0012] Preferably, the mass percentage of the nano metal oxide in the multi-level porous ozone decomposition catalyst is 5% to 30%.

[0013] Preferably, in the mixture of the oxide of metal manganese and the oxide of metal M, the molar ratio of manganese to M is Mn:M=1-30:1.

[0014] Optionally, when the carrier component is a mixed oxide composed of SiO2 or TiO2 and Al2O3, the mass percentage of Al2O3 in the SiO2-Al2O3, TiO2-Al2O3 (mixed oxide) is 60%-95%.

[0015] According to another aspect of the present application, a method for preparing the multi-level porous ozone decomposition catalyst is provided. The method has a simple preparation process, low cost, and is suitable for large-scale industrial production.

[0016] The method for preparing the multi-level porous ozone decomposition catalyst uses water-soluble starch and water-soluble inorganic salt as structure directing agents to construct the primary mesopores and the secondary mesopores;

[0017] The water-soluble inorganic salt is selected from at least one of alkali metal salts and alkaline earth metal salts.

[0018] The method for preparing the multi-level porous ozone decomposition catalyst comprises the following steps:

[0019] a) preparing the carrier

[0020] Pseudo-boehmite is added to a solution containing water-soluble starch to obtain a paste, and the paste is aged, dried, and roasted to obtain the carrier; or

[0021] After mixing a solution containing water-soluble starch with a solution containing a silicon source and / or a titanium source, pseudo-boehmite is added to obtain a paste, and the paste is aged, dried, and calcined to obtain the carrier;

[0022] b) loading the nano metal oxide on the carrier

[0023] The solution containing a manganese source or a solution containing a manganese source and an M source is mixed with the carrier obtained in step a) and a water-soluble inorganic salt; the obtained mixture is ball-milled, washed with water to remove the water-soluble inorganic salt, dried, and calcined to obtain the multi-level porous ozone decomposition catalyst.

[0024] That is, on a carrier with a large mesoporous structure (10-50nm), Mn or Mn-MO with a small mesoporous structure (2-10nm) is loaded in its pores or on its surface by ball milling. x Mixed oxides to form a catalyst with a multi-level mesoporous structure.

[0025] Preferably, the water-soluble inorganic salt is selected from at least one of NaCl, KCl, Na2CO3, K2CO3, CaCl2, and MgCl2.

[0026] Preferably, in step a), the mass ratio of water-soluble starch to pseudo-boehmite is 1 to 50:100; wherein the mass of the pseudo-boehmite is calculated as Al2O3.

[0027] Preferably, in step b), the mass ratio of the M source, the carrier, and the water-soluble inorganic salt is 1% to 20%: 60% to 90%: 1% to 5%.

[0028] Optionally, in step a), the aging time is 10 to 24 hours; the drying temperature is 60 to 120° C., and the drying time is 6 to 8 hours; the roasting temperature is 400 to 650° C., and the roasting time is 2 to 6 hours.

[0029] Optionally, in step b), the ball milling speed is 1000-3000 rpm; the ball milling time is 2-8 hours; the drying temperature is 60-120° C., and the drying time is 6 to 8 hours; the roasting temperature is 300 to 600° C., and the roasting time is 2 to 6 hours.

[0030] According to another aspect of the present application, there is provided an application of the multi-stage porous ozone decomposition catalyst in ozone decomposition in a cabin, indoors, or in the atmosphere, and in catalytic removal of excess ozone during ozone catalytic wet oxidation.

[0031] According to another aspect of the present application, a method for catalytically decomposing ozone is provided, characterized in that the multi-stage porous ozone decomposition catalyst is subjected to reduction treatment and then catalytically decomposes ozone under the following conditions:

[0032] Temperature 0~250℃, ozone concentration 0.1ppm~100ppm, relative humidity 0~100%, volume air velocity 200,000h -1 ~1,000,000h -1 ;

[0033] The reduction treatment comprises subjecting the multi-level porous ozone decomposition catalyst to gas phase reduction at 200-500° C. in an atmosphere containing hydrogen; or subjecting the multi-level porous ozone decomposition catalyst to liquid phase reduction in an aqueous solution containing hydrazine hydrate and / or borohydride.

[0034] Preferably, the reduction treatment includes reducing the multi-level porous ozone decomposition catalyst by gas phase reduction with 10%-100% H2 / N2 mixed gas at 200-500°C before use, or by liquid phase reduction with 2wt.%-10wt.% hydrazine hydrate or sodium borohydride aqueous solution.

[0035] The beneficial effects of this application include but are not limited to:

[0036] (1) The multi-level porous ozone decomposition catalyst provided in the present application has excellent ozone catalytic decomposition performance, especially in a water-containing atmosphere, the ozone decomposition performance can still be maintained.

[0037] (2) The multi-level porous ozone decomposition catalyst provided in the present application has a wide range of applications and can be widely used for ozone removal in various scenarios, including ozone decomposition in cabins, indoors, and in the atmosphere, as well as catalytic removal of excess ozone during ozone catalytic wet oxidation.

[0038] (3) The preparation method of the multi-level porous ozone decomposition catalyst provided in the present application has a simple process, low cost, and is suitable for large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1This is the ozone catalytic decomposition performance of the sample CAT-1 prepared in Example 1 under dry gas conditions.

[0040] Figure 2 The ozone catalytic decomposition performance of sample CAT-2# prepared in Example 2 under dry and wet conditions. DETAILED DESCRIPTION

[0041] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.

[0042] Unless otherwise specified, the raw materials and reagents used in this application were purchased from commercial sources and used directly without treatment. The instruments and equipment used adopted the schemes and parameters recommended by the manufacturers.

[0043] In the embodiment, the ball milling adopts QM-3SP2 high energy ball mill.

[0044] The pore volume and specific surface area were analyzed by BET physical adsorption using Quantachrome NOVA-2000 specific surface area tester.

[0045] As a specific implementation, the preparation method of the multi-level porous ozone decomposition catalyst at least comprises:

[0046] (I) Preparation of porous structure carrier

[0047] A metal salt or soluble silicon is dissolved in a solvent to prepare a 0.1-5.0M metal salt or soluble silicon solution A; a certain amount of starch is dissolved in water to prepare an aqueous solution to prepare a 1.0wt%-20.0wt% starch solution B; the metal solution A and the starch solution B are mixed, and then about 20wt%-95wt.% of pseudo-boehmite (AlOOH) accounting for the weight of the total mixed solution is added while stirring to form a paste C; the paste C is aged at room temperature for 10-24 hours, and then dried at 60-120°C for 2-24 hours, preferably 6-8 hours; then, the carrier D is prepared by calcining at a temperature of 300-650°C for 2-10 hours, preferably calcining at 400-650°C for 2-6 hours.

[0048] The prepared carrier D has a rich mesoporous structure with a pore size of 10 to 50 nm.

[0049] The carrier D may be a SiO2-Al2O3 or TiO2-Al2O3 mixed oxide, wherein Al2O3 accounts for 60%-95% of the mass of the mixed oxide.

[0050] (II) Preparation of multi-level pore ozone decomposition catalyst

[0051] Metal Mn alone or with other metal salt precursors, carrier D, and water-soluble inorganic salts are mixed in a certain ratio, and the above materials are ball-milled in a high-energy ball mill; the water-soluble inorganic salts are removed by water washing, and then drying and calcining are performed to obtain the multi-level porous ozone decomposition catalyst.

[0052] The metal manganese salt includes one or a combination of water-soluble salts such as manganese nitrate, manganese chloride, potassium permanganate, and manganese acetate.

[0053] The metal copper salt includes one or a combination of water-soluble salts such as copper sulfate, copper chloride, copper nitrate, copper carbonate, etc.

[0054] The metal cobalt salt includes one or a combination of water-soluble salts such as cobalt nitrate, cobalt chloride, cobalt sulfate, and cobalt acetate.

[0055] The metal nickel salt includes one or a combination of water-soluble salts such as nickel nitrate, nickel chloride, nickel ammonium sulfate, and basic nickel carbonate.

[0056] The water-soluble inorganic salts include water-soluble salts of alkali metals such as NaCl, KCl, Na2CO3, K2CO3; or water-soluble salts of CaCl2, MgCl2, Ca(NO3)2, Mg(NO3)2, etc., and water-soluble salts of CaCl2, MgCl2, and alkaline earth metals.

[0057] The metal Mn is mixed alone or with other metal salt precursors, carrier D, and water-soluble inorganic salts in a certain ratio, and the atomic ratio of Mn to other metals (M) in Mn-MOx is 1-30, preferably 2-20; the mass ratio of the metal salt precursor, carrier D, and water-soluble inorganic salt is 1% to 20%: 60% to 90%: 1% to 5%.

[0058] The ball milling treatment in the high-energy ball mill has a ball milling speed of 500-3000 rpm and a ball milling time of 2-20 hours; preferably, the ball milling speed is 1000-3000 rpm and the ball milling time is 2-8 hours.

[0059] After the ball milling treatment, the water-soluble inorganic salts are washed to remove the water, and then the product is washed and filtered with deionized water. If the precursor salt contains chloride ions, silver nitrate is used to confirm that there is no chloride ion residue in the filtrate.

[0060] The solid material collected after ball milling and water washing needs to be dried at room temperature-120°C for 2-24 hours, preferably at 60-120°C for 6-8 hours; the roasting temperature is 300-700°C for 2-10 hours, preferably at 300-600°C for 2-6 hours.

[0061] Before use, the catalyst needs to be reduced in gas phase with 10%-100% H2 / N2 mixed gas at 200-500°C for 2-10 hours, or soaked in 2wt.%-10wt.% hydrazine hydrate and sodium borohydride aqueous solution for 24-48 hours, then washed with deionized water, dried at 60-120°C overnight, and then used.

[0062] Example 1 Preparation of sample CAT-1#

[0063] Take 1g of water-soluble starch and dissolve it in water to prepare an aqueous solution, then add 6g of pseudo-boehmite while stirring until a paste is formed; the sample is aged at room temperature for 12 hours, and then dried at 100°C for 8 hours, and then placed in a muffle furnace at 550°C and calcined for 6 hours to obtain a carrier.

[0064] Then, 1g potassium permanganate (KMnO4), 1.87g manganese chloride tetrahydrate (MnCl2·4H2O), and 10g sodium chloride (NaCl) were placed in a ball mill and mixed evenly. Then, 1g of the carrier prepared above was added, and the ball mill was installed on the ball mill. The ball mill was selected for 90min, the speed was 2000rpm, and the cycle was 9 times. Each cycle was first forward for 5min and then reversed for 5min. After ball milling, deionized water was added to the ball mill and ultrasonic was performed to make it easier to separate the powder attached to the wall of the jar and the grinding ball. The obtained powder was washed and filtered with deionized water, and the filtrate was clear. Then, the product obtained by filtration was placed in a 110℃ oven and dried for 4h; the dried sample was calcined at 400℃ for 4h to obtain a catalyst named CAT-1#.

[0065] Example 2 Preparation of Sample CAT-2#

[0066] Take 1g of water-soluble starch and 1.8g of titanium tetrachloride, then dissolve them in water to prepare an aqueous solution, and then add 6g of pseudo-boehmite while stirring until a paste is formed; the sample is aged at room temperature for 12 hours, and then dried at 100°C for 8 hours, and then placed in a muffle furnace at 550°C and calcined for 6 hours to obtain a carrier.

[0067] Then, 1g potassium permanganate (KMnO4), 1.87g manganese chloride tetrahydrate (MnCl2·4H2O), and 10g sodium chloride (NaCl) were placed in a ball mill and mixed evenly. Then, 1g of the carrier prepared above was added, and the ball mill was installed on the ball mill. The ball mill was selected for 90min, the speed was 2000rpm, and the cycle was 9 times. Each cycle was first forward for 5min and then reversed for 5min. After ball milling, deionized water was added to the ball mill and ultrasonic was performed to make it easier to separate the powder attached to the wall of the jar and the grinding ball. The obtained powder was washed and filtered with deionized water, and the filtrate was clear. Then, the product obtained by filtration was placed in a 110℃ oven and dried for 4h; the dried sample was calcined at 400℃ for 4h to obtain a catalyst named CAT-2#.

[0068] Example 3 Preparation of sample CAT-3#

[0069] Take 1g of water-soluble starch and 1.2g of sodium silicate, then dissolve them in water to prepare an aqueous solution, then add 6g of pseudo-boehmite while stirring until a paste is formed; the sample is aged at room temperature for 12 hours, and then dried at 100°C for 8 hours, and then placed in a muffle furnace at 550°C and calcined for 6 hours to obtain a carrier.

[0070] Then, 1g potassium permanganate (KMnO4), 1.87g manganese chloride tetrahydrate (MnCl2·4H2O), and 10g sodium chloride (NaCl) were placed in a ball mill and mixed evenly. Then, 1g of the carrier prepared above was added, and the ball mill was installed on the ball mill. The ball mill was selected for 90min, the speed was 2000rpm, and the cycle was 9 times. Each cycle was first forward for 5min and then reversed for 5min. After ball milling, deionized water was added to the ball mill and ultrasonic was performed to make it easier to separate the powder attached to the wall of the jar and the grinding ball. The obtained powder was washed and filtered with deionized water, and the filtrate was clear. Then, the product obtained by filtration was placed in an oven at 110℃ and dried for 4h; the dried sample was calcined at 400℃ for 4h to obtain a catalyst, named catalyst-3.

[0071] Example 4 Preparation of Sample CAT-4#

[0072] Take 1g of water-soluble starch and dissolve it in water to prepare an aqueous solution, then add 6g of pseudo-boehmite while stirring until a paste is formed; the sample is aged at room temperature for 12 hours, and then dried at 100°C for 8 hours, and then placed in a muffle furnace at 550°C and calcined for 6 hours to obtain a carrier.

[0073] Then, 1g potassium permanganate (KMnO4), 0.935g manganese chloride tetrahydrate (MnCl2·4H2O), 0.33g cupric chloride tetrahydrate (CuCl2·4H2O), 10g sodium chloride (NaCl) were placed in a ball mill and mixed evenly, and then 1g of the carrier prepared above was added, and the ball mill was installed on the ball mill. Ball milling was selected for 90min, the speed was 2000rpm, and the cycle was 9 times. Each cycle was first forward for 5min and then reversed for 5min. After ball milling, deionized water was added to the ball mill and ultrasonic was performed to make it easier to separate the powder attached to the wall of the jar and the grinding ball. The obtained powder was washed and filtered with deionized water, and the filtrate was clear. Then, the product obtained by filtration was placed in a 110℃ oven and dried for 4h; the dried sample was calcined at 400℃ for 4h to obtain a catalyst, named catalyst-4.

[0074] Example 5 Preparation of Sample CAT-5#

[0075] Take 1g of water-soluble starch and dissolve it in water to prepare an aqueous solution, then add 6g of pseudo-boehmite while stirring until a paste is formed; the sample is aged at room temperature for 12 hours, and then dried at 100°C for 8 hours, and then placed in a muffle furnace at 550°C and calcined for 6 hours to obtain a carrier.

[0076] Then, 1g potassium permanganate (KMnO4), 1.246g manganese chloride tetrahydrate (MnCl2·4H2O), 0.425g nickel chloride (NiCl2), 10g sodium chloride (NaCl) were placed in a ball mill and mixed evenly, and then 1g of the carrier prepared above was added, and the ball mill was installed on the ball mill. The ball mill was selected for 90min, the speed was 2000rpm, and the cycle was 9 times. Each cycle was first forward for 5min and then reversed for 5min. After ball milling, deionized water was added to the ball mill and ultrasonic was performed to make it easier to separate the powder attached to the wall of the jar and the grinding ball. The obtained powder was washed and filtered with deionized water, and the filtrate was clear. Then, the product obtained by filtration was placed in a 110℃ oven and dried for 4h; the dried sample was calcined at 400℃ for 4h to obtain a catalyst, named Catalyst-5.

[0077] Example 6 Preparation of Sample CAT-6#

[0078] Take 1g of water-soluble starch and dissolve it in water to prepare an aqueous solution, then add 6g of pseudo-boehmite while stirring until a paste is formed; the sample is aged at room temperature for 12 hours, and then dried at 100°C for 8 hours, and then placed in a muffle furnace at 550°C and calcined for 6 hours to obtain a carrier.

[0079] Then, 1g potassium permanganate (KMnO4), 0.187g manganese chloride tetrahydrate (MnCl2·4H2O), 1.15g cobalt chloride (CoCl2), 10g sodium chloride (NaCl) were placed in a ball mill and mixed evenly, and then 1g of the carrier prepared above was added, and the ball mill was installed on the ball mill. The ball mill was selected for 90min, the speed was 2000rpm, and the cycle was 9 times. Each cycle was first forward for 5min and then reversed for 5min. After ball milling, deionized water was added to the ball mill and ultrasonic was performed to make it easier to separate the powder attached to the wall of the jar and the grinding ball. The obtained powder was washed and filtered with deionized water, and the filtrate was clear. Then, the product obtained by filtration was placed in a 110℃ oven and dried for 4h; the dried sample was calcined at 400℃ for 4h to obtain a catalyst, named catalyst-6.

[0080] Comparative Example 1 Preparation of Sample DCAT-1#

[0081] Pseudoboehmite was calcined in a muffle furnace at 550°C for 3 hours to obtain Then, take 1g potassium permanganate (KMnO4), 1.87g manganese chloride tetrahydrate (MnCl2·4H2O), 10g sodium chloride (NaCl), put them in a ball mill and mix them evenly, then add 1g of the above-prepared The carrier is installed on the ball mill, and the ball mill is selected for 90 minutes, the speed is 2000rpm, and the cycle is 9 times. Each cycle is first forward for 5 minutes and then reversed for 5 minutes. After ball milling, deionized water is added to the ball mill and ultrasonic is performed to make it easier to separate the powder attached to the tank wall and the grinding balls. The obtained powder is washed and filtered with deionized water, and the filtrate is clear. The product obtained by filtration is then placed in an oven at 110℃ and dried for 4 hours; the dried sample is calcined at 400℃ for 4 hours to obtain a catalyst named DCAT-1#.

[0082] Comparative Example 2 Preparation of Sample DCAT-2#

[0083] Take 1g of water-soluble starch and dissolve it in water to prepare an aqueous solution, then add 6g of thin film while stirring until a paste is formed; the sample is aged at room temperature for 12 hours, and then dried at 100°C for 8 hours, and then placed in a muffle furnace at 550°C for calcination for 6 hours to obtain a carrier.

[0084] Take 3.65g potassium permanganate (KMnO4), add 50mL deionized water to fully dissolve it, and obtain solution A. Take 4.34g manganese chloride tetrahydrate (MnCl2·4H2O), 18.25g sodium chloride (NaCl), add 50mL deionized water to obtain solution B. Stir solution B with a magnetic stirrer, add 1g of the above-prepared carrier; and slowly add solution A to the mixture of solution B and carrier by a peristaltic pump within 3h. After the addition is completed, continue stirring for 12h. The obtained suspension is filtered and washed to fully wash away Cl - , and dried in an oven at 100°C for 12 hours; the dried sample was calcined at 400°C for 4 hours to obtain a catalyst named DCAT-2#.

[0085] Example 7 Physical adsorption results of samples CAT-1# to CAT-6#, DCAT-1# and DCAT-2#

[0086] CAT-1#~CAT-6#, DCAT-1# and DCAT-2# were characterized by physical adsorption, and the results showed that CAT-1#~CAT-6# all contained two levels of mesopores. The pore size of the primary mesopores ranged from 10nm to 50nm, with an average pore size of 11nm to 30nm; the pore size of the secondary mesopores ranged from 2nm to 10nm, with an average pore size of 4nm.

[0087] The samples DCAT-1# and DCAT-2# prepared in the comparative example only have mesopores with an average pore diameter of 5 nm.

[0088] Example 8 Catalytic Performance Test (Relative Humidity 50%)

[0089] The samples CAT-1# to CAT-6# obtained in the examples and the samples DCAT-1# and DCAT-2# obtained in the comparative examples were used as catalysts for performance testing. The specific test conditions were as follows: the catalyst dosage was 0.15 g, the reaction stability test temperature was 30°C, the reaction mass space velocity was 600,000 ml.g -1 .h -1 The inlet ozone concentration was 15 ppm, the relative humidity was 50% when testing the wet working condition, and the reactor inlet and outlet gases were analyzed online by a Thermo 49i analyzer. The ozone catalytic decomposition performance and texture parameter results of the above catalysts are shown in Table 1.

[0090] Table 1 Ozone catalytic decomposition performance and pore size of different catalysts

[0091]

[0092]

[0093] Example 9 Catalytic performance test (dry and wet conditions)

[0094] Sample CAT-1# was used as a catalyst to test the ozone catalytic decomposition performance under dry gas conditions. The specific test conditions are as follows: the catalyst dosage is 0.15g, the reaction stability test temperature is 30℃, and the reaction mass space velocity is 600,000ml.g -1 .h -1 The inlet ozone concentration was 15 ppm, the relative humidity was 95% when testing the wet working condition, and the reactor inlet and outlet gases were analyzed online by the Thermo 49i analyzer.

[0095] The results are as follows Figure 1 As shown by Figure 1 It can be seen that under dry gas conditions, the ozone decomposition performance of CAT-1# is very good.

[0096] Sample CAT-2# was used as a catalyst to test the ozone catalytic decomposition performance under dry and wet conditions. The specific test conditions are as follows: the catalyst dosage is 0.15g, the reaction stability test temperature is 30℃, and the reaction mass space velocity is 600,000ml.g -1 .h -1 , the inlet ozone concentration was 15ppm, the relative humidity was 0% during the initial test of the wet working condition, the relative humidity was adjusted to 95% when the reaction time was 12h, and the relative humidity was adjusted to 0% when the reaction time was 24h. The reactor inlet and outlet gases were analyzed online by the Thermo 49i analyzer.

[0097] The results are as follows Figure 2 As shown by Figure 2 It can be seen that CAT-2# can maintain good ozone decomposition performance under both dry and wet conditions, especially under wet conditions, the ozone decomposition performance reaches more than 70% and the performance is stable. When switched to dry gas conditions, the ozone decomposition performance can be quickly restored to the level before the addition of moisture.

[0098] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. A multi-level porous ozone decomposition catalyst, characterized in that: including a carrier and a nano metal oxide; The carrier contains primary mesopores, the pore size of which is 10nm to 50nm; the nano-metal oxide contains secondary mesopores, the pore size of which is 2nm to 10nm; The nano-metal oxide is distributed on the surface of the carrier or in the primary mesopores of the carrier; The nano metal oxide contains metal manganese oxide or a mixture of metal manganese oxide and metal M oxide; the metal M is selected from at least one of Cu, Co, and Ni; The component of the carrier is selected from at least one of Al2O3, SiO2-Al2O3, and TiO2-Al2O3.

2. The multi-level porous ozone decomposition catalyst according to claim 1, characterized in that: The mass percentage of the nano metal oxide in the multi-level porous ozone decomposition catalyst is 5% to 30%; In the mixture of the metal manganese oxide and the metal M oxide, the molar ratio of manganese to M is Mn:M=1-30:1; In the SiO2-Al2O3 and TiO2-Al2O3, the mass percentage of Al2O3 is 60%-95%.

3. A method for preparing the multi-level porous ozone decomposition catalyst according to claim 1 or 2, characterized in that: Using water-soluble starch and water-soluble inorganic salt as structure-directing agents respectively to construct the primary mesopore and the secondary mesopore; The water-soluble inorganic salt is selected from at least one of alkali metal salts and alkaline earth metal salts.

4. The method according to claim 3, characterized in that The following steps are involved: a) preparing the carrier Adding pseudo-boehmite to a solution containing water-soluble starch to obtain a paste, and aging, drying and roasting the paste to obtain the carrier; or After mixing a solution containing water-soluble starch with a solution containing a silicon source and / or a titanium source, pseudo-boehmite is added to obtain a paste, and the paste is aged, dried, and calcined to obtain the carrier; b) loading the nano metal oxide on the carrier The solution containing a manganese source or a solution containing a manganese source and an M source is mixed with the carrier obtained in step a) and a water-soluble inorganic salt; the obtained mixture is ball-milled, washed with water to remove the water-soluble inorganic salt, dried, and calcined to obtain the multi-level porous ozone decomposition catalyst.

5. The method according to claim 3 or 4, characterized in that: The water-soluble inorganic salt is selected from at least one of NaCl, KCl, Na2CO3, K2CO3, CaCl2, and MgCl2.

6. The method according to claim 4, characterized in that In the step a), the mass ratio of water-soluble starch to pseudo-boehmite is 1 to 50:100; Wherein, the mass of the pseudo-boehmite is calculated in terms of Al2O3.

7. The method according to claim 4, characterized in that In the step b), the mass ratio of the M source, the carrier, and the water-soluble inorganic salt is 1% to 20%: 60% to 90%: 1% to 5%.

8. The method according to claim 4, characterized in that In the step a), the aging time is 10 to 24 hours; the drying temperature is 60 to 120° C., and the drying time is 6 to 8 hours; the roasting temperature is 400 to 650° C., and the roasting time is 2 to 6 hours; In the step b), the ball milling speed is 1000-3000 rpm; the ball milling time is 2-8 hours; the drying temperature is 60-120° C., and the drying time is 6-8 hours; the roasting temperature is 300-600° C., and the roasting time is 2-6 hours.

9. Use of the multi-stage porous ozone decomposition catalyst according to claim 1 or 2 in ozone decomposition in a cabin, indoors, or in the atmosphere, and in catalytic removal of excess ozone during ozone catalytic wet oxidation.

10. A method for catalytically decomposing ozone, characterized in that: The multi-stage porous ozone decomposition catalyst according to claim 1 or 2 is used to catalytically decompose ozone under the following conditions after reduction treatment: Temperature 0~250℃, ozone concentration 0.1ppm~100ppm, relative humidity 0~100%, volume air velocity 200,000h -1 ~1,000,000h -1 ; The reduction treatment comprises subjecting the multi-level porous ozone decomposition catalyst to gas phase reduction at 200-500° C. in an atmosphere containing hydrogen; or subjecting the multi-level porous ozone decomposition catalyst to liquid phase reduction in an aqueous solution containing hydrazine hydrate and / or borohydride.